Market-Based Strategy to Anticipate Covid-19 Pandemic in Smallholder Rubber Plantations in Riau Province, Indonesia - Khaswarina, Shorea; Sucherly; Kaltum, Umi; Ariawaty, R Rina Novianti (Asian Journal of Agriculture and Rural Development, 2021)
The coronavirus pandemic had disrupted almost all businesses in various sectors, one of which is the plantation sector. Smallholder rubber plantations in Riau Province, Indonesia have faced the very tough challenges of the coronavirus pandemic. Efforts that could be made were marketing rubber products by implementing market-based strategies, namely market strategy, marketing mix strategy, customer value and marketing performance. This study aimed to analyze the effects of market strategy, marketing mix strategy, and customer value on marketing performance in smallholder rubber plantations in Riau Province during the Covid-19 pandemic. Data collection was carried out using 45 respondents as heads of smallholder rubber plantation farmer groups in Riau Province. Data analysis used structural equation modeling-partial least square (SEM-PLS). The results show that market strategy and marketing mix strategy had a significant direct effect on customer value. Customer value had a significant direct effect on the marketing performance of smallholder rubber plantation farmer groups in Riau, while the market and marketing mix strategies had an indirect effect.